Parameter estimation of a continuous-time plant – the least-absolute error with variable forgetting factor method - Selamat, Hazlina; Yusof, Rubiyah; Goodall, Roger M. (2005)
The least-absolute error with variable forgetting factor (LAE+VFF) estimation method is proposed in this paper to estimate the parameters of time-varying continuous-time (C-T) systems. The algorithm includes an instrumental variable (IV) element to reduce estimation bias and a variable forgetting factor for good parameter tracking and smooth steady state.